Effects of Climate and Atmospheric Nitrogen Deposition on Early to Mid-Term Stage Litter Decomposition Across Biomes - Kwon, TaeOh (2022)
HS and CB acknowledge FCT support to cE3c through UID/BIA/00329/2013, UID/BIA/00329/2019, and UIDB/00329/2020, and the project PORBIOTA - POCI-01- 0145-FEDER-022127.